Business Analysis of Puff Pastry Dough as a Gluten-free Casein-free Diet based on MOCAF Flour and Moringa Leaves for Autism Children - Sunsya Putri Cahyaning Gusti; Ummi Rohajatien; Soenar Soekopitojo; Budi Wibowotomo; Mazarina Devi; Rizki Yulianingrum; Wiwik Wahyuni (Bulletin of Culinary Art and Hospitality, 2021)
Autism Spectrum Disorder (ASD) has a digestive disorder called intestinal mucosal hypermeability, it happens because autism children cannot digest foods that contain gluten and casein, this problem can be overcome by implementing the GFCF (gluten-free casein-free) diet. The purpose of this study was to analyze the dream pastry business opportunity, which is a sheet-shaped puff pastry dough applying GFCF diet therapy. This puff pastry dough is in the shape of a sheet so that it is easy to make creation foods according to the autism children’s favorites. Dream Pastry product design is made from MOCAF flour as a source of gluten-free carbohydrates. It combined with Moringa leaf powder as a natural colorant. Dream Pastry's product development analysis consists of developing product concepts and developing business opportunities. The product concept development consists of processing MOCAF, Moringa leaves to the MOCAF-Moringa combination. Meanwhile, business opportunity analysis uses open a business straight in demand and the analysis of STP (Segmenting, Targeting, Positioning). The analysis were carried out using Market Sizing, while the market potential prediction used TAM (Total Available Market) of autism children recorded in Indonesia as many as 16,987 students. Then, for the SAM (Served Available Market), the author chose East Java as the initial market niche for product distribution. Also, the prediction of sales in the first month called SOM (Share of Market) as many as 106 boxes.